Leader behavior and level of motivation in the Department of Agrarian Reform Regional Office VI - Emano, Lougelyn C.
This study was conducted to find out how leader behavior influences the level of motivation of the Department of Agrarian Reform Regional Office VI (DARRO VI) employees to perform well in their work. Specifically, this study aimed to describe the leadership behaviors of supervisors at DARRO VI, to find out the level of motivation of DARRO VI employees to perform well in their work, and to recommend measures to improve their level of motivation and work performance. The results of the study showed that supervisors at the DARRO VI exhibited supportive, directive, achievement-oriented and participative leader behaviors. These leader behaviors were manifested in different ways. The respondents mostly rated their supervisors "Very Satisfactory" in all of the mentioned leader behaviors. These leader behaviors influenced the respondents to perform well in their work as indicated by high levels of confidence to achieve work output. at the same time, the respondents had rated their work performance " Very Satisfactory" which is corroborated by their past office performance evaluation ratings. Problems that affect their motivation were the non-adressing of the issue on the equity of workload assignments, lack of appreciation for the work that they are doing, indecisiveness, and involvement of personal issues with work. Leader behaviors that motivate the respondents to perform well were supportive, encouraging friendly, open to suggestions, knowledgeable, professional, and responsive to employee needs. It is recommended that the supervisor should take time to observe and know each of his or her subordinate's unique personality and needs in order to motivate him or her. Likewise, the supervisor should be fair and professional in dealing with his or her subordinates. Good working relationships must also be developed and maintained. The agency's management should also provide support to its middle managers by enhancing their leadership capabilities through trainings.